The Role of Environmental Uncertainty, Green HRM and Green SCM in Influencing Organization’s Energy Efficacy and Environmental Performance - Lee, Hoyoung (International Journal of Energy Economics and Policy, 2020)
Environment sustainability is becoming a global issue which urge the organizations to transform their existing operations towards more environmental friendly. It is not just required by the regulatory bodies by the end consumers also demands manufacturer to produce more environment friendly goods. Hence the present research studies the role of Green Supply Chain Management, Green Human Resource Management and Environment Uncertainty was examined and their effect on Environment performance and energy efficiency was evaluated. By employing quantitative research methodology, by means of survey questionnaire the data was collected and the sample of 378 was driven on which PLS-SEM was applied as statistical technique. The results have shown the significantly positive role of GSCM, GHRM and ENUN on ENPR and ENEF. The study conclude that the organizations should implement more green initiatives in the SCM, human resources and other financial resources for the human health and environment. Keywords: Green Supply Chain Management; Green Human Resource Management; Environment Uncertainty; Environment performance; energy efficiency. JEL Classifications: O13, O44, D20 DOI: https://doi.org/10.32479/ijeep.9221